EPEN-23. Interaction of epigenetic regulation and telomerase re-activation in high-risk ependymoma. (3rd June 2022) - Jaunecker, Carola N; Kirchhofer, Dominik; Madlener, Sibylle; Laemmerer, Anna; Gabler, Lisa; Pirker, Christine; Piontek, Martin; Maaß, Kendra; Okonechnikov, Konstanitin; Englinger, Bernhard; Jiang, Li; Mayr, Lisa; et al.
Abstract: Ependymomas (EPN) account for 10% of pediatric CNS tumors. Among the ten subgroups characterized by DNA methylation profiling, tumors located in the supratentorial region that harbor ZFTA fusions (e.g. ZFTA-RELA), and tumors in the posterior fossa region group A (PF-A) represent the most aggressive entities. As currently therapy success relies on the extent of tumor resection and druggable targets are so far widely missing, new therapeutic approaches are urgently needed. Epigenetic dysfunction, resulting in aberrant histone modifications as well as altered DNA methylation patterns, majorly contributes to the aggressiveness of high-risk EPN. In earlier studies, we discovered that high-risk EPN is composed of a cellular hierarchy initiating from stem-cell like populations, frequently showing telomerase re-activation. Considering that epigenetic mechanisms regulate stemness maintenance and telomerase reverse transcriptase (TERT), we studied the impact of epigenetically active drugs on differentiation and telomerase re-activation in these tumors. Accordingly, we first investigated the basal expression levels of TERT and EZH2 in a panel of patient-derived high-risk EPN cell models of different subtypes (n=7). Interestingly, both, TERT and EZH2, were highly expressed predominantly in ZFTA-RELA cell models. Corroboratively, increased sensitivity of ZFTA-RELA cells towards the EZH2 inhibitor DZNep was observed in cell viability and clonogenic assays. While HDAC inhibitors were similarly active across high-risk EPN cell models, the BET inhibitor JQ1 more efficiently reduced survival of ZFTA-RELA cells. Treatment with DZNep resulted in a loss of H3K27me3 histone marks accompanied by decreased ubiquitination of H2AK119 in the investigated ZFTA-RELA cell models, and induced apoptosis indicated by PARP cleavage. Currently, impacts of direct or pharmacological EZH2 blockade on TERT promoter methylation, induction of senescence and differentiation are analyzed. Summarizing, we proof varying efficacy of epigenetically active drugs in high-risk EPN subgroups, in particular EZH2 inhibition in ZFTA-RELA cell models.